The value of Diethylstilbestrol implants and implants plus an Antibiotic for wintering steer calves - Smith, E.F.; Koch, B.A.; Richardson, D.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Forty-four good-to-choice Hereford steer calves from near Fort Davis, Texas, were randomly allotted according to weight to three treatments. All lots were fed the same high roughage rations. They received per head daily: 5 pounds of sorghum grain and 1 pound of soybean meal. Sorghum silage was fed according to appetite, and salt was offered free choice.
Keywords: Beef; Diethylstilbestrol implants; Antibiotic; Gain